What Did the Psalmist Say about His Hands and Feet in Psalm 22:17? - Flowers, Michael V. (Vetus Testamentum, 2021)
Abstract Ps 22:17 is among the most controverted verses in the Hebrew Bible, both with respect to its original text and original meaning. The biggest question that text critics and interpreters struggle to answer is what the psalmist said concerning his hands and feet. With so many proposals now on the table and with debates on this text having reached an impasse, it seemed like it would be helpful to present the status quaestionis with regard to this text. Thirteen different proposals are therefore analyzed with a view to their respective merits and demerits. The goal here is to eliminate the proposals that seem least viable and to become more self-conscious about how we judge between the others.